(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Genetic diversity among 24 spring wheat genotypes (Varieties/lines) was estimated using Mahalanobis D2-statistics and principal coordinate analysis. The genotypes fell into four clusters of different size. Of the seven different characters spike length and 1000 grain weight had the highest contribution towards the divergence. The highest inter cluster distance was observed between cluster I and III followed by cluster II and III. So, genotypes from the most divergence clusters could be used as parents in hybridization program and are expected to manifest maximum heterosis as well as broad spectrum of variability.